A community-based cluster randomised controlled trial in rural Bangladesh to evaluate the impact of the use of iron-folic acid supplements early in pregnancy on the risk of neonatal mortality: the Shonjibon trial - Tanvir M. Huda; Mohammad Masudur Rahman; Shahreen Raihana; Sajia Islam; Tazeen Tahsina; Ashraful Alam; Kingsley Agho; Sabrina Rasheed; Alison Hayes; Mohd Anisul Karim; Qazi Sadequr Rahman; Abu Bakkar Siddique; et al. (BMC, 2018)
Abstract Background Iron-deficiency is the most common nutritional deficiency globally. Due to the high iron requirements for pregnancy, it is highly prevalent and severe in pregnant women. There is strong evidence that maternal iron deficiency anaemia increases the risk of adverse perinatal outcomes. However, most of the evidence is from observational epidemiological studies except for a very few randomised controlled trials. IFA supplements have also been found to reduce the preterm delivery rate and neonatal mortality attributable to prematurity and birth asphyxia. These results combined indicate that IFA supplements in populations of iron-deficient pregnant women could lead to a decrease in the number of neonatal deaths mediated by reduced rates of preterm delivery. In this paper, we describe the protocol of a community-based cluster randomised controlled trial that aims to evaluate the impact of maternal antenatal IFA supplements on perinatal outcomes. Methods/design The effect of the early use of iron-folic acid supplements on neonatal mortality will be examined using a community based, cluster randomised controlled trial in five districts with 30,000 live births. In intervention clusters trained BRAC village volunteers will identify pregnant women & provide iron-folic acid supplements. Groundwater iron levels will be measured in all study households using a validated test kit. The analysis will follow the intention to treat principle. We will compare neonatal mortality rates & their 95% confidence intervals adjusted for clustering between treatment groups in each groundwater iron-level group. Cox proportional hazards mixed models will be used for mortality outcomes & will include groundwater iron level as an interaction term in the mortality model. Discussion This paper aims to describe the study protocol of a community based randomised controlled trial evaluating the impact of the use of iron-folic acid supplements early in pregnancy on the risk of neonatal mortality. This study is critical because it will determine if antenatal IFA supplements commenced in the first trimester of pregnancy, rather than later, will significantly reduce neonatal deaths in the first month of life, and if this approach is cost-effective. Trial registration This trial has been registered with the Australian New Zealand Clinical Trials Registry (ANZCTR) on 31 May 2012. The registration ID is ACTRN12612000588897.